2000
DOI: 10.1123/ssj.17.3.254
|View full text |Cite
|
Sign up to set email alerts
|

“Just Do It”: Consumption, Commitment, and Identity in the Windsurfing Subculture

Abstract: Debates about changing contemporary Western societies have emphasized the increasingly fluid and fragmented nature of identities, suggesting that people draw their sense of identity from increasingly diverse sources, including sport and leisure lifestyles. Drawing on ethnographic work on windsurfing subcultures, this article explores the ways in which participants create and perform (sub)cultural identities through their “new sport” consumption and its attendant lifestyle. The paper identifies the main feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(96 citation statements)
references
References 0 publications
5
82
0
9
Order By: Relevance
“…Unnecessarily expensive boards that are well preserved indicate that they are not frequently used and that the person does not know how to surf but wants to appear to be a surfer for its supposed appeal outside the sports universe. A similar situation was noted by Wheaton (2000) with regard to windsurfing:…”
Section: Surfing Is No Longer Only a "Playboy" Thingsupporting
confidence: 75%
See 1 more Smart Citation
“…Unnecessarily expensive boards that are well preserved indicate that they are not frequently used and that the person does not know how to surf but wants to appear to be a surfer for its supposed appeal outside the sports universe. A similar situation was noted by Wheaton (2000) with regard to windsurfing:…”
Section: Surfing Is No Longer Only a "Playboy" Thingsupporting
confidence: 75%
“…Because I did not have experience with surfing, as opposed to Wheaton (2000), the participant observation strategy of analysis required learning (similar to Wacquant, 2002) how to surf. As a result, I would be able to watch and hear what surfers did and said while they waited for waves at the sea and to use my body as a source of experiential data to provide better descriptions.…”
Section: Methodsmentioning
confidence: 99%
“…Il s'agit de prendre à contrepied la marchandisation engendrée par l'intégration des activités de nature initialement conçues dans une logique alternative (Loret, 1995) au sein de l'industrie des loisirs et du tourisme de nature (Dienot & Theiller, 1992;Perrin & Mounet, 2004). Effectivement, la littérature sociologique en France ou au plan international (Lacroix, 1988;Nasser, 1996;Wheaton, 2000;Weed, 2008) montre bien comment ces activités de nature, surf, windsurf, deltaplane, parapente, escalade, rafting… sont paradoxalement devenues un secteur commercial en magazines, vêtements de mode, matériel technique ou destinations de voyage. En France, le canyoning, avec seulement 24 % de la fréquentation des sites composée de pratiquants indépendants, contre 67 % de clients d'une structure commerciale (Suchet & Jorand, 2009), repré-sente d'ailleurs l'une des activités particulièrement illustrative de ce phénomène.…”
Section: Une Forme Originale De Rejet Du Système éConomique Marchandunclassified
“…Based on a route of 174 km, the Marmotte takes cyclists over some of the most famous cols of the Tour De France and it enables cycle tourists the chance to participate in a planned ride covering the same terrain that professional cyclists follow, and is a combination of what Gibson (2005) refers to as active sports tourism and nostalgia, combining participation with an element of vicarious adoration. Such events are reflective of a challenge culture that is not dissimilar to that discussed in the analysis of extreme and lifestyle sports where groups of individuals are undertaking more and more physically extreme activities that differentiate them from the mainstream cultural experience (Wheaton, 2000). Research on such event experiences lacks any real attempt to employ a multidisciplinary approach that considers, at the outset, the experiences to be multidimensional and multiphasic and to consequently develop a methodological mix that would give deeper meaning and insight into these variable components within has shown that experience is not static, that it is multidimensional and is always open to the effects of participants' interaction (Botterill & Crompton, 1996;Hull, Michael, Walker, & Roggenbuck 1996;Y.…”
Section: Planning and Staging Event Experiencesmentioning
confidence: 99%